Integrating AI and IoT with Salesforce: A Framework for Digital Transformation in the Manufacturing Industry - Potla, Ravi Teja (Journal of Science & Technology, 2023)
In the rapidly evolving manufacturing industry, the integration of Artificial Intelligence (AI) and the Internet of Things (IoT) with Customer Relationship Management (CRM) platforms like Salesforce has become essential for driving digital transformation. This paper presents a comprehensive framework for leveraging AI and IoT technologies within Salesforce to enhance operational efficiency, optimize production processes, and improve product quality. By analyzing real-time data collected from IoT devices and applying AI-driven analytics within Salesforce, manufacturers can gain actionable insights, reduce downtime, and streamline their operations. A case study of a leading manufacturing company demonstrates the practical application of this framework, highlighting significant improvements in production efficiency and product quality. The paper also explores the broader implications of this integration for various industries, offering a scalable and adaptable model for digital transformation.
Keywords: AI; IoT; Salesforce; Digital Transformation; Manufacturing; Operational Efficiency; CRM